Analisis Konten dalam Strategi Keamanan Siber Kuwait Berdasarkan Teori Three Perspective Theory of Cyber Sovereignty - Afrizal Fajri (Insignia: Journal of International Relations, 2021)
This research seeks to analyze Kuwait's cybersecurity strategy in its cybersecurity document using content analysis methods in understanding the focus and approach taken by the Kuwait’s government. The theoretical framework used in this research uses Three Perspective Theory of Cyber Sovereignty which explains the division of layers in the context of sovereignty in cyberspace. The method used is a mixed method to determine which aspects and approaches are more dominant in the Kuwaiti government policy to manage cyber space in the country. Results of this study indicate that Kuwait tends to take policies that are in the exclusive layer. The main aspect is in terms of preventing threats that can exist through cyberspace. This shows that Kuwait's cyberspace policy tends to be exclusive, in the sense that the state must be present and regulate most of the cyberspace area.